Kajian Futuristik Dan Hubungannya Dengan Pembangunan Peradaban Islam Di Malaysia (The Futuristic Study and The Relationship with the Development of Islamic Culture in Malaysia) - Hernawati Nasir; Suraya Sintang (2018)
This paper discusses the future study and its relations to the development of civilization of Islam in Malaysia. The viewpoint of the future study is examined from the perspective of Muslim contemporary futurist, Ziauddin Sardar. The method used is content analysis by exploring the futuristic ideas of previous prime ministers during their administrative periods; initiation of the Vision 2020 by Tun Dr Mahathir Mohamad, the conception of Islam Hadhari by Tun Abdullah Ahmad Badawi and the establishment of Transformation by Dato’ Najib Tun Razak. The finding shows that the strategy towards formation the developed country has clearly been seen in the transition of the Malay to the urban area where they still manage to maintain the lifestyle of Islam as they are living in the village. The study concludes that Malaysia will achieve the target to be developed country with the Islamic values in the life of the Malays.